Sistem Informasi Akuntansi Penjualan Alat Pemadam Kebakaran pada PT Sinar Surya Semestaraya - Dahlia , Dahlia; Lestari , Endah Wiji; Herlinawati , Nuraeni; Leliyanah , Leliyanah (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Information technology, especially in the field of computer technology, has developed very rapidly which has brought to the new world, communication plays an important role in life. Various facilities are provided to meet all communication needs, especially sales. This can be seen from the many places that provide internet facilities to obtain information, which can be enjoyed by all groups at an affordable cost. PT. Sinar Surya Semestaraya is a company that sells fire extinguishers. The sales system is still not computerized, so it is difficult to record sales transactions and manage sales reports resulting in miscalculations due to employee negligence. This is less effective and efficient, because it is difficult to record and calculate the number of types of goods that exist. The large number of items sold and the crowd of buyers can make it difficult for sellers to organize and calculate sales transactions quickly, precisely and efficiently. The solution to the problem is utilizing accounting information systems, especially the sale of fire extinguishers. Through computerization, it is hoped that it will make it easier for consumers to make the purchasing process and get complete information. Information on product names is available using a website-based sales application program. Companies can market one product to consumers with a wide range, so that from a business perspective it is a good opportunity to expand product sales marketing.